Framing Influences Willingness to Pay but Not Willingness to Accept. (December 2013) - Yang, Yang; Vosgerau, Joachim; Loewenstein, George
The authors show, with real and hypothetical payoffs, that consumers are willing to pay substantially less for a risky prospect when it is called a "lottery ticket, " "raffle, " "coin flip, " or "gamble" than when it is labeled a "gift certificate" or "voucher." Willingness to accept, in contrast, is not affected by these frames. This differential framing effect is the result of an aversion to bad deals, which causes buyers to focus on different aspects than sellers. Buyers' willingness to pay is influenced by the extent to which a risky prospect's frame is associated with risk (Experiment 1) as well as the prospect's lowest (but not highest) possible outcome (Experiment 2). Sellers' willingness to accept, in contrast, is influenced by a prospect's lowest and highest possible outcomes but not by the risk associated with its frame (Experiments 2 and 3). The framing effect on willingness to pay is independent of the objective level of uncertainty (Experiment 4) and can lead to the uncertainty effect. The findings have important implications for research on risk preferences and marketing practice.